PEMBUKTIAN ALAT BUKTI DALAM TRANSAKSI ELEKTRONIK SEBAGAI AKIBAT WANPRESTASI - Sadinah Sadinah (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTIn meeting the needs of every day people always need others, both in meeting the needs of primary and secondary and tertiary needs. In this modern age, people use the covenant as one form of binding between one party and another, this is done in an attempt to avoid self-disputes. On the other hand, the agreement occurs because both parties do want each other and have a high level of dependence between each other.Pardon actually can be used as a recovering agency to correct "errors" in the implementation of the law. Although there is already a herziening institute that can be used by the convicted person, but clemency that is outside the legal domain and outside of this criminal justice system, can be a president as a means to correct and demonstrate his legal wisdom. In America as a developed country where the level of prudence and control over its law enforcers is very high, the occurrence of errors in the law is still very high as well. Things like this could happen in Indonesia. It is the duty of the President to treat doubts about possible legal weaknesses. So that clemency can reflect the level of wisdom of the President and the society.